Women's Experiences in Managing Small Businesses in The Digital Age: a Narrative Approach - Yuliastuti, Hilda; Rosalia, Olyvia (Nomico, 2025)
This study explores women's experiences in managing small businesses in the digital age using a narrative approach. By collecting in-depth stories from female entrepreneurs, the research highlights how digital technologies such as social media, e-commerce platforms, and digital business tools have transformed the way women operate and grow their businesses. The findings reveal that digitalization has opened up new market opportunities, enhanced business efficiency, and empowered women to innovate and assert greater autonomy in their entrepreneurial roles. However, challenges such as digital literacy gaps, limited financial resources, and socio-cultural constraints remain prevalent. Despite these barriers, many women demonstrate resilience and adaptability, especially when supported by family, community networks, and access to digital training. The study underscores the importance of integrating digital support systems into entrepreneurship development programs to foster inclusive economic empowerment. Overall, digitalization emerges not only as a technical tool but also as a strategic means to advance gender equality in the economic sector.